UX (USER EXPERIENCE) EVALUATION OF THE OPENLEARNING SYSTEM AT UNIVERSITAS MUHAMMADIYAH SURAKARTA USING HEURISTIC EVALUATION AND USABILITY TESTING - Imana, Afifah Ghaisani; Nugroho , Yusuf Sulistyo (Informatika, Universitas Jenderal Soedirman, 2023)
Since the COVID-19 pandemic in 2020, the learning process at the University of Muhammadiyah Surakarta (UMS) has been carried out online using the OpenLearning platform. The use of OpenLearning media has provided an easy learning process for both lecturers and students. Although there are many conveniences and benefits offered, usability problems still arise, for example, there is no distinction between courses that have ended and those that are still active, the